Stable isotopes infer the diet and habitat of the enigmatic pygmy right whale (Caperea marginata) off southern Australia - Dedden, Adelaide V.; Kemper, Catherine M.; Truong, Gary; McCurry, Matthew R.; van Ruth, Paul D.; Rogers, Tracey L. (Frontiers in Marine Science, 2023)
In the Southern Hemisphere, baleen whales generally undertake migrations between productive feeding grounds at high latitudes and breeding grounds at lower latitudes. Pygmy right whales (Caperea marginata) (PRW) are the smallest and most enigmatic baleen whale, that likely forgo long-distance migrations, and instead inhabit temperate and subantarctic waters year-round. Previous research has relied on limited data from sighting and stranding records to infer the habitat use and diet of PRWs, however the absence of long-term and consistent data has left uncertainty surrounding these parameters. We utilized bulk stable isotopes of carbon (δ13C) and nitrogen (δ15N) in baleen from Australian PRWs (n = 14) to infer their diet and habitat use. Stable isotope values from 1980–2019 were then matched to remote sensed data from known upwelling regions (where they likely feed) to examine if their dietary patterns are related to changes in food web dynamics. We found that PRWs remained in mid-latitude waters year-round and showed no evidence of feeding in Antarctic waters. Rather, their isotopic record suggests they remain between coastal waters off southern Australia and the Subtropical Convergence, feeding on krill and copepods. Additionally, there was a weak positive relationship between PRW nitrogen stable isotope values and sea surface temperature (SST) from the eastern Great Australian Bight (GAB) and Bonney Upwelling. This suggests seasonal changes in their diet is possibly correlated to oceanographic changes which drive food-web dynamics in these regions. Unlike larger species of baleen whales that migrate further to highly productive waters in the Southern Ocean to meet their energetic demands, the small PRW, who only reach 6.5m, may sustain both feeding and breeding requirements at mid-latitudes. This is the first study to analyze long-term dietary and movement patterns of the PRW, providing an important contribution to our understanding of the species.